Occupational Risk Factors and Preventive Measures for COVID-19 In Prosthodontics - Thammareddy, Tharuni; Sujesh, M; Ravikumar, C; Zakkula , Srujana (International Journal of Dental Materials, 2020)
Today, novel coronavirus infection has become pandemic worldwide. It is the major cause of sickness from the common cold to severe acute respiratory syndrome in individuals. In a dental operatory, infections can be expedited through several routes like aerosol generation, contaminated surfaces, droplet splatter, oral fluids, and direct contact. Keeping in mind about the routes of transmission of COVID-19 (Coronavirus disease-19), dental practitioners are at higher risk of exposure and disease spread. Hence, this review article emphasizes the routes of transmission, risk factors, prophylactic and preventive measures. It also sights on alternative approaches to prosthodontic procedures to reduce the burden of COVID-19 infection in their community. Data acquisition was made using the keywords, COVID-19, infection control, prosthodontic risk factors in electronic databases like PubMed, Medline, ProQuest, etc. A manual search of several journals and books was also carried out, and only highly relevant articles were considered for the present review.